Magnetic properties of on-surface synthesized single-ion molecular magnets. Issue 59 (25th October 2019) - Diller, Katharina; Singha, Aparajita; Pivetta, Marina; Wäckerlin, Christian; Hellwig, Raphael; Verdini, Alberto; Cossaro, Albano; Floreano, Luca; Vélez-Fort, Emilio; Dreiser, Jan; Rusponi, Stefano; Brune, Harald
Abstract : We perform on-surface synthesis of single-ion molecular magnets on an Ag(111) surface and characterize their morphology, chemistry, and magnetism. Abstract : We perform on-surface synthesis of single-ion molecular magnets on an Ag(111) surface and characterize their morphology, chemistry, and magnetism. The first molecule we synthesize is TbPc2 to enable comparison with chemically synthesized and subsequently surface adsorbed species. We demonstrate the formation of TbPc2 with a yield close to 100% and show that on-surface synthesis leads to identical magnetic and morphological properties compared to the previously studied chemically synthesized species. Moreover, exposure of the surface adsorbed TbPc2 molecules to air does not modify their magnetic and morphological properties. To demonstrate the versatility of our approach, we synthesize novel Tb double deckers using tert -butyl-substituted phthalocyanine (tbu-2H-Pc). The Tb(tbu-Pc)2 molecules exhibit magnetic hysteresis and therefore are the first purely on-surface synthesized single ion magnet.